Re-enchanting modernity : ritual economy and society in Wenzhou, China - Yang, Mayfair Mei-hui (Duke University Press, 2020)
"RE-ENCHANTING MODERNITY is based on over twenty-five years of ethnography in the Chinese coastal city of Wenzhou and the surrounding towns. Combining methods from anthropology, religious studies, and history, author Mayfair Yang traces the reemergence of religious life and ritual following long periods of attempted secularization in China. She shows that rather than being opposed to the massive capitalist growth which has occurred in the Wenzhou region, these religious imaginaries and ritual practices are embedded in and inform economic development. Yang is interested in what motivates the return of these rituals in post-Maoist China and their complex relation to capitalist expansion in the area, one that as might be expected is different than the Weberian model from the west. She examines how gender is re-figured in the contemporary versions of these religious practices, given the changes in gender attitudes in the intervening years. Yang concludes that a scholar's notion of civil society must include religious and quasi-religious institutions - even, as in Wenzhou, when they are describing intensively modernized locations. After an opening placing the book amid current social theory, chapter one gives a brief social history of religious culture and secularization in Wenzhou from the late nineteenth century to the present and discusses Yang's ethnographic experience. Chapter two lays out the dynamic local economy of post-Mao Wenzhou that sets the context for the resurgence of ritual and religious life. The chapters which immediately follow provide ethnographic and historical accounts of different forms of religious and ritual life in contemporary Wenzhou: Popular Religion, Daoism, and Buddhism. Chapter six deals with grassroots-initiated temple organizations and religious associations, which, Yang proposes, represent an indigenous and religious civil society. Chapter seven focuses on the activities of the Wang Lineage revival in Longwan District as an example of other lineage revivals. Men are at the forefront of lineage revival, with its patrilineal descent favoring the birth of sons. Yang discusses the gender dimension of religious revival and the tensions between kinship and religious institutions in terms of gendered agency. Chapter eight addresses rural women's religious agency in spearheading temple reconstruction and launching religious civil society. It explores female agency in Wenzhou-- which is often conservative, modest, and self-sacrificing-- and the crucial role of women in fueling the religious drive. Chapter nine examines the ritualization of "the local" and of "community," and it calls for a broadening of the modern category of "civil society" to accommodate the particular conditions of non-Western, non-urban, and religious cultures. Finally, chapter ten examines how the ritual economy is at the same time a stimulus for, a product of, and a counter-movement to the conventionally understood capitalist market. This book will be of interest in anthropology, religious studies and Asian studies, as well as to theorists interested capitalism's relation to religion"--